The Effect of Adding Pine Tar Oil and Petrosin as Tackifier Ingredients on The Quality of Liquid Rubber Compound-based Adhesives - Umi Alma Anggraini; Teja Dwi Sutanto; Irfan Gustian; Morina Adfa; Evi Maryanti (Jurnal Kimia Sains dan Aplikasi, 2023)
This research is focused on the development of adhesives through the utilization of different types of tackifiers. The primary raw materials employed comprise 60% concentrated latex, which is subsequently blended with additives that have been dispersed, including KOH as a stabilizing agent, stearic acid and ZnO as activators, BHT as an antioxidant, CaCO3 as a filler, MBTS (Mercaptobenzothiazole disulfide) and TMTD (Tetramethyl Thiuram Disulphide) as accelerators, and sulfur as a vulcanizing agent. This research explored two specific variations of tackifiers: pine tar oil and petrosin. The characterization of the adhesives encompasses an analysis of acidity (pH), viscosity, adhesive strength, functional group analysis using FTIR, thermal properties, and XRD. The research findings showed that the optimal conditions were achieved in the third variation of the adhesive, with the same ratio of pine tar oil tackifier and petrosin of 4 grams each. In this particular variation, adhesives conforming to the SNI 12- 7195-2006 standards were produced, displaying an adhesion strength of 1.506 N/mm, a viscosity of 1075 cP, and a pH level of 4.6. Furthermore, thermal testing results reveal that the adhesive created with tackifier (V3) exhibits thermal resistance up to 350°C, a glass transition temperature of 354°C, and a melting point of 378°C.